2017
DOI: 10.4018/ijrqeh.2017040105
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Intelligence Approach to Thrombophilia Risk

Abstract: Thrombophilia stands for a genetic or an acquired tendency to hypercoagulable states, frequently as venous thrombosis. Venous thromboembolism, represented mainly by deep venous thrombosis and pulmonary embolism, is often a chronic illness, associated with high morbidity and mortality. Therefore, it is crucial to identify the cause of the disease, the most appropriate treatment, the length of treatment or prevent a thrombotic recurrence. This work will focus on the development of a diagnosis decision support sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The artificial neural networks (ANNs) approach to data processing enables not only that data are processed in a system context but also to capture complex or unknown relationships between inputs and outputs (Vicente et al 2012;Vilhena et al 2017). ANNs simulate the structure of the human brain, being populated by artificial neurons, with a valuable set of activation functions (Haykin 2009).…”
Section: Artificial Neural Network Approach To Computingmentioning
confidence: 99%
See 3 more Smart Citations
“…The artificial neural networks (ANNs) approach to data processing enables not only that data are processed in a system context but also to capture complex or unknown relationships between inputs and outputs (Vicente et al 2012;Vilhena et al 2017). ANNs simulate the structure of the human brain, being populated by artificial neurons, with a valuable set of activation functions (Haykin 2009).…”
Section: Artificial Neural Network Approach To Computingmentioning
confidence: 99%
“…Typically used is a hillclimbing approach that begins with an initial architecture that is adjusted with the purpose of decreasing the internal measure of error (e.g., the mean squared error) (Haykin 2009). In recent years, several studies have demonstrated the effectiveness of ANNs in multiple contexts such as environment (Ahmed 2017;Ruben et al 2018), health (Vilhena et al 2017;Neves et al 2018), and education (Figueiredo et al 2020).…”
Section: Artificial Neural Network Approach To Computingmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the difficulty of use, lack of support for job performance, and inability to meet expectations, employees' dissatisfaction with AI security technologies has a negative effect on their intention to use them in the future.With regard to balancing the world's superpowers and maintaining its security in the future, the UAE will face challenges related to its geographic scope and military's ability to employ modern technology. However, there are few empirical studies on the service quality (SQ) of artificial intelligence (AI) used by government agencies in the United Arab Emirates to safeguard properties (Salih et al, 2017) and effectiveness of AI services available in the United Arab Emirates (Vilhena et al, 2017).…”
mentioning
confidence: 99%